1998
DOI: 10.1007/s002469900347
|View full text |Cite
|
Sign up to set email alerts
|

Child Homicide Caused by Commotio Cordis

Abstract: Cardiac concussion, previously known as commotio cordis, occurs in structurally normal hearts without gross or microscopic injury to the myocardium, cardiac valves, or coronary arteries, as opposed to other sports-related deaths known to occur more frequently in structural or congenital heart disease. We describe the sudden cardiac death of a 2-year-old child, who died as a result of a blunt force impact to the chest. A thorough medicolegal investigation was necessary to determine that the child died as a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…By contrast, it has also been suggested as underlying an extra cardiac phenomenon described as "commotio cordis" or cardiac concussion (17), in which a blunt impact to the front of the chest produces arrhythmic death without structural damage, often in children or young adults during sports injuries (1,24). It also occurs in adults and can have medicolegal implications (2,10).…”
mentioning
confidence: 99%
“…By contrast, it has also been suggested as underlying an extra cardiac phenomenon described as "commotio cordis" or cardiac concussion (17), in which a blunt impact to the front of the chest produces arrhythmic death without structural damage, often in children or young adults during sports injuries (1,24). It also occurs in adults and can have medicolegal implications (2,10).…”
mentioning
confidence: 99%
“…11 Different criteria have been proposed by multiple research teams. Maron et al 12 suggested the flowing inclusion criteria for commotio cordis from 128 confirmed cases: (1) a witnessed blunt, non-penetrating blow to the chest immediately preceding cardiovascular collapse; (2) detailed documentation of the circumstances from available newspaper articles, police reports and telephone interviews with family members or other witnesses; (3) absence of structural damage to the sternum, ribs and heart itself; and (4) absence of any underlying cardiovascular abnormalities. The present victim collapsed immediately after suffering from a blunt blow to the chest within several minutes, which was similar to other victims.…”
Section: Discussionmentioning
confidence: 99%
“…Link and colleagues found that a normal baseball with 40 mph/sec was apt to trigger ventricular fibrillation compared to the same baseball with 70 mph/sec, which mainly lead to recruitment of stretch-activated ion channels during the 15-30 msec window prior to the T-wave in the cardiac cycle (3,5). Most decedents due to commotio cordis were men and showed a predilection for children and adolescents (1,9,10). In the current cases, both decedents were exactly 15-year-old males.…”
Section: Discussionmentioning
confidence: 99%